Physiological Principle of Tactual Discriminability of Fabric Surface Softness by Touching Method (Journal of Fiber Bioengineering and Informatics, 2008)
Fabric Softness is one of main factors in guiding consumers' purchasing decisions, andmany instrumental testing techniques quantifying this attribute have been proposed to substitute forits sensory evaluation. However, the performance is poor. By establishing a biomechanical modelequivalent to the manner in which human fingertips sense the mechanical resistance against lateralcompression of fabric, this study theoretically discusses the mechanical sensitivity of human sensingorgans and the perceptual sensitivity of human sensory system. The results show that the mechanicalsensitivity depends on the ratio of the mechanical resistance against compression of fabric to thatof fingerpad, and the perceptual sensitivity on both the mechanical sensitivity and the capacity ofhuman tactile system. Furthermore, the scatter among individual tactile evaluation on softness isattributed to the limitation of human tactile system processing stimulus information, and the assignedmagnitude principally obeys a certain probability distribution, not a single averaging value statistically.In this sense, the deformability of soft tissues leads to an intrinsic difference of tactile evaluationfrom instrumental testing, although fabric compression property is detected on the same mechanicalprinciple. The present conclusions will correct our misunderstandings in the effect-cause relationshipbetween sensory attributes and instrumental testing.